The Implementation of the Patient’s Privacy Regulations in The People’s Republic of China - Ghozali, Falah Al; Hardyanthi, Try; Fadhilah, Sarah (Indonesian Comparative Law Review, 2020)
The right to privacy, especially with regard to personal health condition, seems to be an issue in China. Illegal access to personal information and illegal disclosure of personal information to others constitute the infringement of the Personal Privacy Act. Although the privacy right has been governed under the Constitution since the 1980’s, however, its implementation has not yet been satisfactory due to some reasons. This paper aims to describe the implementation of the patient’s privacy regulations in the People’s Republic of China. This normative legal research employing a descriptive-qualitative method. The study shows that the right to privacy for the patients in China needs to get more attention from government, medical personnel and ruling groups.